The assessment of the urban landscape and its relationship with the state of conservation of the monumental area of ​​Tacna in 2016 - Gambetta Quelopana, Renza Lourdes (2017)
The objective of the research is to establish the relationship between the level of assessment and the level of conservation status in the Tacna Monumental Zone in 2016. Research applied and quantitative, descriptive and correlational. The instrument was made from models applied by the Spanish Municipalities, which are based in turn on the European Landscape Model. Validated by expert judgment. Pearson's linear correlation coefficient was used to identify the correlation between the variables analyzed. The results reflect a relationship between the valuation variable and the conservation status variable, applied to the case study of the Tacna Monumental Zone. It was concluded that there is a direct and significant relationship between the assessment of the urban landscape and the state of conservation of the Tacna Monumental Zone in 2016 (Pearson correlation of 0.936 and significance value of 0.01).